Reasons for high divorce rates in Palestine from the point of view of legal lawyers in some governorates of northern Palestine - Iyad mohamed fiyad AIMAOUI (Social Sciences Journal, 1970)
This study seeks to identify the reasons which cause the high divorce rates inPalestine from the immigrant lawyers, viewpoint in some northern districts ofPalestine, the study used the descriptive method, and the researcher used acomprehensive survey style of the community study of lawyers component of (105)lawyers, during the month of January 2016, using the questionnaire as a tool tocollect information related to the study. The findings: found that the overall level ofthe reasons for the high divorce rates in the view of immigrants lawyers inPalestine was high, and the total score for all areas of study (78.16%), and that themain reasons for the high divorce rates depending on the areas were as follows:the technological reasons (IT), which was the most important reason for the highdivorce rates, (82.88%), the social reasons, the self and psychological reasons,religious reasons, and finally economic reasons. the study also highlighted a set ofrecommendations to reduce the problem of high divorce rates in Palestine.